t(4) = 2^(3) + (2^(3) - 1) // Math makes sense, but why did we decide to represent 8 as an 2 to the 3rd? Is the goal to find exponential representations? t(4) = 2^(4-1) + (2^(4-1) - 1) // Why on earth did we decide 3 is better represented as 4-1??

Hold that thought right there. The reason why we use 4-1 instead of 3 is to represent the value of n in the formula, so we can write n-1. Because in that example, n = 4.

If you notice in my previous comment, my goal was not simply to solve the equation with several values of n, but to show how the result and the parameters of the function relate each other.

The goal of the deduction process is to find the function that solves these relations: t(1) = 1 + 0 // same as 2^(1-1) + (2^(1-1) - 1)
t(2) = 2 + 1 // same as 2^(2-1) + (2^(2-1) - 1)
t(3) = 4 + 3 // same as 2^(3-1) + (2^(3-1) - 1)
t(4) = 8 + 7 // same as 2^(4-1) + (2^(4-1) - 1)
t(5) = 16 + 15 // same as 2^(5-1) + (2^(5-1) - 1)

That way you can find a function that solves for every value of n. Please let me know if I now made it clear.

We're a place where coders share, stay up-to-date and grow their careers.

Hold that thought right there. The reason why we use

`4-1`

instead of`3`

is to represent the value of`n`

in the formula, so we can write`n-1`

. Because in that example,`n = 4`

.If you notice in my previous comment, my goal was not simply to solve the equation with several values of

`n`

, but to show how the result and the parameters of the function relate each other.The goal of the deduction process is to find the function that solves these relations:

`t(1) = 1 + 0 // same as 2^(1-1) + (2^(1-1) - 1)`

t(2) = 2 + 1 // same as 2^(2-1) + (2^(2-1) - 1)

t(3) = 4 + 3 // same as 2^(3-1) + (2^(3-1) - 1)

t(4) = 8 + 7 // same as 2^(4-1) + (2^(4-1) - 1)

t(5) = 16 + 15 // same as 2^(5-1) + (2^(5-1) - 1)

That way you can find a function that solves for every value of

`n`

. Please let me know if I now made it clear.